1989
DOI: 10.1210/jcem-68-6-1073
|View full text |Cite
|
Sign up to set email alerts
|

Periovulatory Follicular Fluid Hormone Levels in Spontaneous Human Cycles*

Abstract: We measured follicular fluid hormone levels in 48 normally cycling infertile women who underwent follicle puncture and oocyte retrieval during diagnostic laparoscopy at time-bracketed intervals after an endogenous LH surge. Follicular fluid LH, FSH, PRL, estrone (E1), estradiol (E2), progesterone (P), androstenedione (A), and testosterone (T) concentrations and P/E2 and A/E2 ratios were determined. Oocytes were classified as germinal vesicle (gv), metaphase I (mI), metaphase II (mII), or degenerating (dg). Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…Several investigators have demonstrated that mature oocytes with a higher potential for fertilization are also associated with lower testosterone levels in FF at the time of follicular rupture (20,21). Our results are in agreement with these data.…”
Section: Discussionsupporting
confidence: 93%
“…Several investigators have demonstrated that mature oocytes with a higher potential for fertilization are also associated with lower testosterone levels in FF at the time of follicular rupture (20,21). Our results are in agreement with these data.…”
Section: Discussionsupporting
confidence: 93%
“…Large (Ͼ8 mm diameter) follicles in the mid-and late follicular phase of the menstrual cycle contain appreciable (up to 10,000-fold) higher quantities of E 2 compared with small follicles, as has been shown by numerous authors (60, 75,76,[83][84][85][86][87]. Intrafollicular E 2 concentrations were up to 40,000-fold higher than those in peripheral plasma, and 20-fold higher concentrations of E 2 have been observed in venous blood draining the ovary containing the dominant follicle as compared with the contralateral side (88,89).…”
Section: B Intrafollicular Endocrine Changessupporting
confidence: 54%
“…A number of studies have examined the prolactin concentration of follicular fluid in maturing ova. Generally, a higher level of prolactin is seen in follicles containing mature oocytes capable of being fertilized (Laufer et al 1984;Bohnet et al 1985;Reinthaller et al 1987a,b;Gonen and Casper 1989;Seibel et al 1989;Oda et al 1991;Yoshimura et al 1991), although others find no relationship (Messinis and Templeton 1987) or suggest a negative effect (Irahara et al 1991). Using immature eggs collected from mouse ovaries, prolactin was found to increase the rate of germinal vesicle breakdown and subsequent fertilization and correct development in vitro (Randall et al 1990).…”
Section: Oocyte Maturationmentioning
confidence: 99%